2005
DOI: 10.1002/jctb.1253
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic reduction of N2O with CH4 and C3H6 over Ag–Rh/Al2O3 bimetallic catalyst in the presence of oxygen

Abstract: A study of nitrous oxide (N 2 O) reduction with methane (CH 4 ) and propene (C 3 H 6 ) in the presence of oxygen (5%) over Ag/Al 2 O 3 , Rh/Al 2 O 3 and Ag-Rh/Al 2 O 3 catalysts, with Ag and Rh loadings of 5 wt% and 0.05 wt% respectively, has been performed. From the results, it was observed that the Ag-Rh bimetallic catalyst was the most active for both nitrous oxide removal (more than 95%) and hydrocarbon oxidation. This high activity seems to be connected with a synergistic effect between Ag and Rh. The fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…54 It was reported that bimetallic Ag-Rh/Al 2 O 3 catalyst (undefined Ag-Rh structure) exhibited higher activity (for both nitrous oxide removal and hydrocarbon oxidation) than the monometallic counterparts for nitrous oxide (N 2 O) reduction with methane and propene in the presence of oxygen (5%), due to the synergistic effect between Ag and Rh. 55 Afterwards, an ultrasound-assisted membrane reduction (UAMR) method was developed to construct highly dispersed Rh/g-Al 2 O 3 and bimetallic Au-Rh/g-Al 2 O 3 catalysts. The synergistic effect of the bimetallic system was found to improve the performance of selective catalytic reduction of NO and reduce the cost for Pt group metal-based catalysts.…”
Section: Alloy Nps Involving Two Noble Metalsmentioning
confidence: 99%
“…54 It was reported that bimetallic Ag-Rh/Al 2 O 3 catalyst (undefined Ag-Rh structure) exhibited higher activity (for both nitrous oxide removal and hydrocarbon oxidation) than the monometallic counterparts for nitrous oxide (N 2 O) reduction with methane and propene in the presence of oxygen (5%), due to the synergistic effect between Ag and Rh. 55 Afterwards, an ultrasound-assisted membrane reduction (UAMR) method was developed to construct highly dispersed Rh/g-Al 2 O 3 and bimetallic Au-Rh/g-Al 2 O 3 catalysts. The synergistic effect of the bimetallic system was found to improve the performance of selective catalytic reduction of NO and reduce the cost for Pt group metal-based catalysts.…”
Section: Alloy Nps Involving Two Noble Metalsmentioning
confidence: 99%
“…Although the material obtained by radiolysis showed a significantly higher activity than a sample obtained by a conventional technique, its activity was not satisfactory with T 50 of approximately 510 °C (0.5 g of catalyst, 0.5 vol % N 2 O/He, 60 cm 3 min −1 total flow rate). Tzitzios et al . studied deN 2 O over Ag‐(Pd/Rh) supported on γ ‐ Al 2 O 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Ramnani et al [17] showedt he advantage of radiolysis over impregnation for the preparation of (5.0 wt %) Ag supported on SiO 2 .A lthough the material obtained by radiolysis showeda significantly highera ctivity than as ample obtained by ac onventional technique, its activity was not satisfactory with T 50 of approximately 510 8C( 0.5 go fc atalyst, 0.5 vol %N 2 O/He, 60 cm 3 min À1 total flow rate). Tzitzios et al [18][19][20] studied deN 2 O over Ag-(Pd/Rh) supported on g-Al 2 O 3 .A gd eposited on Al 2 O 3 showedp oor catalytic activity,a nd the catalyst suffered from strong O 2 inhibition (N 2 Oc onversion at6 47 8Cd ecreased from > 50 to 15 %i nt he presence of O 2 ). However,b imetallic sys-N 2 Oi sapotent greenhouse gas released among others in nitric and adipic acid production as well as from stationary and mobile combustion sources.…”
mentioning
confidence: 99%
“…It has been well documented in literature that the alloy surfaces often lead to superior activity and selectivity because of the modification of the relative stability of the reactants due to the possible ligand effects, strain effects, and ensemble effects induced by the second elements. [16][17][18][19][20][21][22][23][24][25] Particularly, the ability of alloy surfaces with multiple adsorption sites and reaction centers are thought to be crucial for the catalysts with desired selectivity and free of poisons. [26][27][28] In this work, an extensive set of atomic ͑H, C, N, O, S͒, molecular ͑N 2 , CO, NO͒, and radical ͑OH and CH 3 ͒ species on RhMn͑111͒ surface alloy is studied by density functional theory ͑DFT͒ calculations in terms of their energetics, adsorption sites, and structures, supplemented with detailed electronic structural analysis.…”
Section: Introductionmentioning
confidence: 99%